The Use of C4.5 Algorithm for Classification of New Student Admissions in Vocational High Schools: Case Study: Piramida Rancaekek Vocational High School - Budiman, Dheni Apriantsani; Indiani, Sri Rahayu (Jurnal Computech & Bisnis (e-journal), 2025)
The New Student Admission is a mandatory process conducted by all educational institutions to maintain the continuity of student cohorts within the educational framework.  At Vocational High School Piramida, The New Student Admission process adheres to a traditional methodology, resulting in subjective and protracted selection procedures.  Consequently, the author employs the C4.5 algorithm as a classification technique that produces decision trees from potential student data.  The created system is intended to manage The New Student Admission process with greater efficiency and objectivity.  This study utilizes descriptive analysis, and the system development adheres to Object-Oriented Software Engineering (OOSE) principles.  The system architecture employs the PHP programming language in conjunction with the Laravel framework and a MySQL database.  This study demonstrates that utilizing the C4.5 algorithm can enhance the efficiency and effectiveness of the student selection process, reduce errors, expedite data administration, and lead to a more objective student selection process.  The method enhances information accessibility for prospective students, consequently augmenting its attractiveness to candidates.